Fixation Design Device On Child Support Radiographs Patient Safety and Safety Radiation - Siti Masrochah; Yeti Kartikasari; Ardi Soesilo Wibowo (Poltekkes Kemenkes Semarang, 2013)
This research is a descriptive exploratory. The procedure is done by designing data collection tools, further trials with 20 samples. Function test results aids fixation is to have an average score of 2.66, which means good. While the test results for each component, the majority of respondents stated that the reliability of the device is quite good with a score of 2.45 (60%), convenience tool with a score of 2.60 (70%), quality of the radiographs with a score 2.55 (85%), the child protection (security) with a score of 2.70 (70%), good design aesthetic design with a score of 2.80 (80%), addition of radiation from the others on the use of these tools do not need with a score of 2.80 (80%), and there is no additional radiation due to repetitions with a score of 2.85 (90%).